The European Union's China policy: Priorities and strategies for the new commission - Guy De Jonquières (European Centre for International Political Economy (ECIPE), 2015)
The arrival of a new European Commission is a good opportunity for Europe to re-consider its policy vis-à-vis China. Under Xi Jinping, China is going through a period of change in domestic as well as foreign policy - and this change adds urgency to Europe's quest for an effective China policy. If Europe wants to carry weight in its relation with China, it first needs to set its house in order. The Eurozone's crisis and the lack of economic vitality are not just causing worries in Beijing; they also undermine Europe's standing in China as a powerful entity to deal with. Europe's absence as a strategic and military power in the Asian region makes its economic health all the more important if it wants to get listened to a country that prizes power. The European Union should prioritise its trade and investment ambitions with China. These are the areas where the European treaties endow the EU institutions with power. China has great stakes in its commercial relation to Europe and if the EU acts skillfully it can obtain improvements in its access to China's market. However, Europe needs to formulate a policy that does not split its own ranks. It needs to be able to speak with one voice and not give China the opportunity to play the game of divide and rule with Europe. China can play that game skillfully and did that in several trade-defence disputes with Europe during the previous Commission. Beyond trade and investment, it needs to put the emphasis on areas of cooperation where the two sides share ambitions.
Keywords: 330; Internationale Zusammenarbeit; Außenpolitik; EU-Staaten; China